Two novel mutations in ADAMTS13 in a Chinese boy with congenital thrombocytopenic purpura: a case report - Ling Hou; Yue Du (BMC, 2020)
Abstract Background Mutations in the ADAMTS13 gene family have been reported to cause congenital thrombotic thrombocytopenic purpura (cTTP), a rare disease characterized by thrombocytopenia and hemolytic anemia. Nearly 150 causative mutations in ADAMTS13 have been identified; however, only a few of them were detected in Chinese patients. Case presentation A 5-year-old Chinese boy presented with history of thrombocytopenic purpura, hemolytic anemia, and renal injury since the neonatal period. Gene analysis revealed two novel mutations in ADAMTS13: a missense mutation 332G > A (p:Gly111Glu) in exon4 and a nonsense mutation 3121C > T (p:Gln1041stop) in exon 24. Genetic analysis of his parents confirmed the heterozygous nature of the mutations. Conclusion We report two novel mutations in ADAMTS13 (332G > A, 3121C > T) in a Chinese boy. These two mutations may lead to early onset of cTTP and severe symptoms.